Biochemical and microbiological quality of fermented silage prepared from dressing waste of Indian major carps using different concentrations of jaggery - Tanuja, S.; Kumar, Anil; Sarkar, A.; Nayak, Sujit K. (Indian Journal of Fisheries, 2016)
Present study investigated the shelf life of fermented silage prepared from dressing waste (gut and gills) of Indian major carps and the effect of different concentrations of jaggery as carbohydrate source, on the biochemical and microbiological changes in the silage. Fermented silage was prepared using jaggery at 10% w/w (F1) and 20% w/w (F2) concentrations. F2 had a lower crude fat and ash content. The lowest pH attained was 4.11 and 4.02 in F1 and F2 respectively by the end of 15 days. Significantly higher (p<0.05) concentration of total volatile base nitrogen (TVB-N) was observed in F2 from the 30th day of storage. The rate of auto-oxidation was also significantly higher in F2 throughout the storage period of 60 days. Total plate count (TPC) of bacteria in F1 and F2 reduced significantly till the 15th day of storage. At the end of 60 days of storage, pH reached 5.55 and 5.67 in F1 and F2 respectively, thereafter the silage was considered spoiled. The study indicated that fermented fish silage prepared from viscera and gills of Indian major caps remained shelf worthy for a period of 60 days and the use of jaggery at concentrations higher than 20% (w/w) would not be viable as it led to faster spoilage rate and increased cost of production